Size effects of polycrystalline lanthanum modified Bi4Ti3O12 thin films - Simões, Alexandre Zirpoli [UNESP]; Riccardi, C. S. [UNESP]; Cavalcante, L. S.; Gonzalez, A. H. M. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The film thickness dependence on the ferroelectric properties of lanthanum modified bismuth titanate Bi3.25La0.75Ti3O12 was investigated. Films with thicknesses ranging from 230 to 404 nut were grown on platinum-coated silicon substrates by the polymeric precursor method. The internal strain is strongly influenced by the film thickness. The morphology of the film changes as the number of layers increases indicating a thickness dependent grain size. The leakage current, remanent polarization and drive voltage were also affected by the film thickness. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: thin films; chemical synthesis; atomic force microscopy; dielectric properties